Pengembangan Usaha UKM Kedai Kopi Abang Kecamatan Pulogadung Dengan Metode Business Model Canvas - Febriansyah, Febriansyah (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
This community service program (PKM) is set up to improve the business development of the Kedai Kopi Abang UKM Pulo Gadung District with the Business Model Canvas method. PKM partners are men and women with an age range of 20-30 years. They are the owners and employees of small and medium business units under the name Kedai Kopi Abang. The implementation method used in this PKM activity is training on the topic of the business model canvas as a strategy for creating product differentiation to develop businesses. The results achieved from this activity include: ongoing cooperation with other SME entrepreneurs; SMEs do have differentiated products that are different and superior to similar products owned by competitors; and SMEs can utilize digital marketing channels in developing their businesses primarily in building consumer relationships through Instagram social media Keywords: business model canvas, SME’s